Copper matte - slag reaction sequences and separation processes in matte smelting - Guntoro P.I.; Jokilaakso A.; Hellstén N.; Taskinen P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
While particle combustion and chalcopyrite oxidation in suspension smelting is well understood, few studies are available regarding the melt-melt reactions and the separation between copper matte and slag in matte smelting. In the present work, experimental investigations in air and argon atmosphere were conducted using a mixture of synthetic slag and chalcopyrite concentrate. The sequential reaction and separation processes occurring in matte smelting are outlined. Possible limiting factors in the overall process are also proposed. The result of the present work forms an important foundation for future work in the kinetic rate formulation of molten phase reactions between copper matte and slag in matte smelting.